2021
DOI: 10.51791/njap.v26i1.3021
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Graded Levels of Brewears’ Spent Grains and Kolaunt Pod Meal on the Performance Characteristic and Carcass Quality Rabbits

Abstract: Thirty six New Zealand fryer rabbit (bucks) averaging 874g in body weight were fed on three diets blended with 0, 7, 14% kolaunt pod meal (KPM) and10, 20, and 30% Brewers spent grains (BSG). Other dietary components included maize, soyabean meal, bone meal, salt and vitamin-mineral mixture. The trail lasted for 98 day. Significantly differences (P < 0.05) were found among the three rations with respect to daily live weight gains, feed intake and water intake. There were significant difference among the rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Heart weight fluctuated across dietary treatments. It also negate findings of Oluokun and Olaolu (1999) who reported that increased heart weight of rabbit fed 10% cashew nut meal residue based diet increased metabolic activities of liver. The study disagreed with the findings of Ojewola and Ewa (2005) who reported that the quality and fat content of the cashew kernel meal (15.54%) elicited increased activity in the heart of the chicken fed diet four, thus leading to increase observed in the weight of heart in birds fed diet four which is numerical and respectively above those of diets 5, diet 3, 2 and 1 respectively.…”
Section: Discussioncontrasting
confidence: 65%
“…Heart weight fluctuated across dietary treatments. It also negate findings of Oluokun and Olaolu (1999) who reported that increased heart weight of rabbit fed 10% cashew nut meal residue based diet increased metabolic activities of liver. The study disagreed with the findings of Ojewola and Ewa (2005) who reported that the quality and fat content of the cashew kernel meal (15.54%) elicited increased activity in the heart of the chicken fed diet four, thus leading to increase observed in the weight of heart in birds fed diet four which is numerical and respectively above those of diets 5, diet 3, 2 and 1 respectively.…”
Section: Discussioncontrasting
confidence: 65%
“…The proximate composition of brewer's dried grain (BDG), which is maize/sorghum-based, includes 28.25% CP, 13.12% CF, 6.70% EE, 7.36% total Ash, and 4.23 Kcal/gram of gross energy, according to Uchegbu and Udedibie (1998). However, the nutrient composition of BDG differs depending on the grain source and brewing method (Oluokun and Olalokun, 1995). In many towns in Nigeria's rice-growing regions, rice offal is readily available throughout the year and is high in lysine and methionine content (Makinde et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ivory Coast, Ghana, Brazil and the West Indian Islands also cultivate kolanut [3]. Nigeria produces two million metric tons of kolanut annually which represented 70% of the world's kolanuts production [4]. According to [5], there are about 40 kola nut species dominant in West Africa while the kola species of economic importance especially in Nigeria, West and Central Africa, the Caribbean Islands, Mauritius, Sri Lanka and Malaysia are Cola acuminate and Cola nitida.…”
Section: Introductionmentioning
confidence: 99%